Small bowel adenocarcinoma: revisited - Rosley, Muhammad F.; Dissanayake, Mahanama (International Surgery Journal, 2021)
Small bowel malignancies are rare despite it representing 75% of the gastro intestinal (GI) length and 90% of the mucosal surface area. Even then small bowel adenocarcinoma (SBA) accounts for only 30-40% of all small intestine malignancies. Etiology is multifactorial and risk factors include hereditary mutations, inflammatory bowel diseases, coeliac disease. Presenting symptoms are vague and nonspecific and cannot usually be diagnosed by conventional upper and lower GI endoscopy as it is in an inaccessible location. This leads to delayed diagnosis and hence poor prognosis. Mainstay of treatment is surgical resection with adjuvant chemotherapy in advanced disease. We present a case study of a 74 years old woman who presented to the emergency department with small bowel obstruction and radiological features suggestive of underlying small bowel malignancy. She underwent urgent laparotomy with segmental small bowel resection and had intraoperative evidence of wide spread metastasis which was confirmed on subsequent tumor staging scans. She received adjuvant chemotherapy with complete metabolic response at one year post resection. SBA is generally diagnosed at advanced stage due to its anatomical location. Complete surgical resections should always be targeted. However, adjuvant chemotherapy plays a role in advanced disease even though clinical data of evidence is scarce.